Cognitive Task Demands Modulate the Sensitivity of the Human Cochlea - Smith, David W.; Aouad, Rony K.; Keil, Andreas (Frontiers in Psychology, 2012)
Recent studies lead to the conclusion that focused attention, through the activity of corticofugal and medial olivocochlear efferent pathways, modulates activity at the most peripheral aspects of the auditory system within the cochlea. In two experiments we investigated the effects of different intermodal attention manipulations on the response of outer hair cells (OHCs), and the control exerted by the medial olivocochlear (MOC) efferent system. The effect of the MOCs on OHC activity was characterized by measuring the amplitude and rapid adaptation time course of distortion product otoacoustic emissions (DPOAEs). In the first, DPOAE recordings were compared while participants were reading a book and counting the occurrence of the letter “a” (auditory ignoring) and while counting the either short- or long-duration eliciting tones (auditory attending). In the second, DPOAEs were recorded while subjects watched muted movies with subtitles (auditory ignoring/visual distraction) and were compared with DPOAEs recorded while subjects counted the same tones (auditory attending) as in experiment 1. In both experiments 1 and 2, the absolute level of the averaged DPOAEs recorded during the auditory-ignoring condition was statistically higher than that recorded in the auditory-attending condition. Efferent-induced rapid adaptation was evident in all DPOAE contours, under all attention conditions, suggesting that two medial efferent processes act independently to determine rapid adaptation, which is unaffected by attention, and the overall DPOAE level, which is significantly affected by changes in the focus of attention.